The Invention of Jealousy - Konstan, David (2005)
In this paper the A. proposes the idea that, in classical Greece, the concept of a feeling that exactly corresponds to Jealousy in the modern Western world. did not exist. He inquires on the meaning of the word zélotupia that is frequently translated by "jealousy", and proves that it did not have that precise meaning in the ancient Greek texts. Yet, although there was little room in archalc Greek culture for the developmenl of the idea of Jealousy in a romantic sense. in Rome's first century B.C., conditions favoured the development of such a concept, concretely in Horace's amatory poems and in the authors of erotic elegy.